2007
DOI: 10.1007/s00442-007-0816-x
|View full text |Cite
|
Sign up to set email alerts
|

Niche diversity in crustacean cryptic species: complementarity in spatial distribution and predation risk

Abstract: Recent genetic studies indicate that species with very close phenotypic similarity ("cryptic species") are a common feature of nature, and that such cryptic species often coexist in communities. Because traditional views of species coexistence demand that species differ in phenotype to coexist stably, the existence of sympatric cryptic species appears to challenge traditional perspectives of coexistence. We evaluated niche diversity in three recently discovered species of Hyalella amphipods that occur sympatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 46 publications
1
58
0
1
Order By: Relevance
“…However, recent genetic studies using different molecular markers [12,[19][20][21][22] and interbreeding trials [23] revealed that they were in fact a cryptic species complex composed of at least 33 provisional species [21]; this number is probably an underestimate as it was found by a study limited to the southern Great Basin region of California and Nevada [21]. Cryptic species of Hyalella amphipods often live in sympatry at the same site in a water body [6,21]. A recent study by Wellborn and Cothran [6] suggests that Hyalella cryptic species can, in some cases, exhibit niche partitioning despite being similar in morphology and life history [6,12].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…However, recent genetic studies using different molecular markers [12,[19][20][21][22] and interbreeding trials [23] revealed that they were in fact a cryptic species complex composed of at least 33 provisional species [21]; this number is probably an underestimate as it was found by a study limited to the southern Great Basin region of California and Nevada [21]. Cryptic species of Hyalella amphipods often live in sympatry at the same site in a water body [6,21]. A recent study by Wellborn and Cothran [6] suggests that Hyalella cryptic species can, in some cases, exhibit niche partitioning despite being similar in morphology and life history [6,12].…”
Section: Introductionmentioning
confidence: 77%
“…The fact that many cryptic species live in sympatry challenges our traditional view of how species assemble [4][5][6]. To coexist at the local scale, species must be ecologically distinct in a manner that makes intraspecific competition more important for the population of a species than interspecific competition [7].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The general view, in the face of interspecific competition, is that the primary way to achieve this coexistence is for species to show a differential use of resources (Hutchinson 1961, Schoener 1974, Pyke 1982, Young et al 2010. However, the fact that many sympatric species do not appear to differ sufficiently in their morphology to allow for niche differentiation (Wellborn and Cothran 2007) has challenged this view.…”
Section: Introductionmentioning
confidence: 96%
“…Apesar de vários estudos criticarem o modelo de equilíbrio em comunidades (e.g., Strong 1982, Strong et al 1984, Wiens et al 1986, Eterovick & Barros 2003 alguns artigos recentes têm demonstrado coexistência baseada em diferenciação de nicho (e.g., Elliot & Mariscal 2001, Menin et al 2005, Verburg & Bills 2007, inclusive entre espécies crípticas (Nicholls & Racey 2006, Wellborn & Cothran 2007.…”
Section: Introductionunclassified